Rosemary as ecologically acceptable corrosion inhibitor of steel - Ćatić, Sead; Obralić, Ema; Bratovčić, Amra (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2016)
In recent years, due to increasing interest and attention of the world towards environmental protection, there has been a complete reduction or use of a certain number of corrosion inhibitors. Corrosion inhibitors are substances which, added in small quantities in aggressive media, may greatly reduce the rate of corrosion of metals. In the development of corrosion inhibitors, it is necessary to pay special attention to their toxicity and impact on environmental pollution. The research of plant extracts have become a great area of interest in the study of corrosion inhibitors. Testing the ability to protect steel was performed with plant material (Rosmarinus officinalis L.). In order to determine the basic parameters that show the effectiveness of green inhibitors, electrochemical measurements of corrosion rate were carried out. Results obtained by DC techniques (method of Tafel extrapolation) showed that the corrosion rate decreases in the presence of the tested corrosion inhibitor. Studies have shown that, in a certain concentration, rosemary (Rosmarinus officinalis L.) has the effectiveness of the protection of steel in 3% NaCl, and as such, it is considered an acceptable corrosion inhibitor.